2015
DOI: 10.1056/nejmoa1414219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Red-Cell Storage Duration on Patients Undergoing Cardiac Surgery

Abstract: BACKGROUND Some observational studies have reported that transfusion of red-cell units that have been stored for more than 2 to 3 weeks is associated with serious, even fatal, adverse events. Patients undergoingcardiac surgery may be especially vulnerable to the adverse effects of transfusion. METHODS We conducted a randomized trial at multiple sites from 2010 to 2014. Participants 12 years of age or older who were undergoing complex cardiac surgery and were likely to undergo transfusion of red cells were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
425
2
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 426 publications
(461 citation statements)
references
References 26 publications
17
425
2
5
Order By: Relevance
“…Whether and how the stiffness of RBCs changes during storage has critical relevance to patient safety and treatment effectiveness in transfusion medicine 6,47 . RBCs over the storage process have been mechanically characterized in both stretching and folding modes, and different metrics for indicating RBC deformability were used 17,18,48 .…”
Section: Rbc Effective Stiffness Increases During Storagementioning
confidence: 99%
“…Whether and how the stiffness of RBCs changes during storage has critical relevance to patient safety and treatment effectiveness in transfusion medicine 6,47 . RBCs over the storage process have been mechanically characterized in both stretching and folding modes, and different metrics for indicating RBC deformability were used 17,18,48 .…”
Section: Rbc Effective Stiffness Increases During Storagementioning
confidence: 99%
“…16 The clinical implication of "old" RBC units is a controversial issue, because results provided by retrospective studies and randomized clinical trials are not in agreement. [18][19][20][21][22][23][24][25][26][27] Even if the full clinical impact of the storage lesion 28 and, specifically, of this multiphase metabolic decay, remains to be elucidated, it can be argued that all the metabolomics studies performed so far showed almost complete overlap of metabolic profiles of RBCs stored in different storage additives, despite interlaboratory strategies and metabolomics platforms. 13 For these reasons, we believe that an underlying signature of the RBC storage lesion exists across various media solutions and processing techniques, and that it can be translated in biomarkers that define the metabolic stage of stored RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently trial after trial are currently showing no differences between groups causing confusion and misinterpretation in the field especially in relation blood transfusions. For example another US trial published in the NEJM by Steiner et al (9) almost identical to the Koch study except that they used leuco-reduced blood, could not reproduce the Koch findings instead finding no difference in outcome when aged red blood cells were transfused in cardiac surgery patients (9). Lacroix et al (10) also could not reproduce the results in cardiac surgery concerning the age of red blood cells.…”
Section: Nüzhet Mert şEntürk Editormentioning
confidence: 99%